2015
DOI: 10.1002/fld.3997
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of droplet ejection of thermal inkjet printheads

Abstract: Summary In this study, we present a method to predict the droplet ejection in thermal inkjet printheads including the growth and collapse of a vapor bubble and refill of the firing chamber. The three‐dimensional Navier–Stokes equations are solved using a finite‐volume approach with a fixed Cartesian mesh. The piecewise‐linear interface calculation‐based volume‐of‐fluid method is employed to track and reconstruct the ink–air interface. A geometrical computation based on Lagrangian advection is used to compute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 62 publications
(85 reference statements)
2
16
0
1
Order By: Relevance
“…The final speed of projectile is approximately ~12m/ s which agrees with previous numerical and experimental studies [11, 15, 43, 44]. The drop head velocity at any instance of time is depicted in Fig.…”
Section: Thermal Inkjet Printersupporting
confidence: 88%
See 4 more Smart Citations
“…The final speed of projectile is approximately ~12m/ s which agrees with previous numerical and experimental studies [11, 15, 43, 44]. The drop head velocity at any instance of time is depicted in Fig.…”
Section: Thermal Inkjet Printersupporting
confidence: 88%
“…Moreover, the geometry of their printhead is significantly more complicated compared to HP60. Although different print head geometry is used in our simulation, it is observed that our numerical results roughly matches the experimental result and CFD simulation of Tan et al [43]. The main reason for lower printhead velocity is using nozzle with bigger diameter, 48μm, compared to Tan et al work [3] where it was 20 μm .…”
Section: Thermal Inkjet Printersupporting
confidence: 78%
See 3 more Smart Citations